2018
DOI: 10.1016/j.jdermsci.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and pharmacological assessment of murine IL-23 mediated psoriasiform dermatitis; implications for drug discovery

Abstract: Collectively, our studies indicate that a 5 day model of IL-23 psoriasiform dermatitis can be used to assess the pharmacology of novel small molecules/biologics in the treatment of PsO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 33 publications
(40 reference statements)
8
31
1
Order By: Relevance
“…Direct intradermal injection of IL‐36α into mouse ears produced a robust inflammatory response as evidenced by ear swelling, epidermal thickening/keratinocyte proliferation, macrophage accumulation, immune cell accumulation/proliferation (also in DLN) and increased expression of IL‐17A, IL‐6, IL‐22, CXCL1, S100a7a and Defb4, which are genes/pathways associated with psoriatic inflammation . The increased expression of IL‐17A and IL‐22 supports previous findings that IL‐36 cytokines potentiate the production of Th17 cytokines contributing to the cytokine network in psoriasis .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Direct intradermal injection of IL‐36α into mouse ears produced a robust inflammatory response as evidenced by ear swelling, epidermal thickening/keratinocyte proliferation, macrophage accumulation, immune cell accumulation/proliferation (also in DLN) and increased expression of IL‐17A, IL‐6, IL‐22, CXCL1, S100a7a and Defb4, which are genes/pathways associated with psoriatic inflammation . The increased expression of IL‐17A and IL‐22 supports previous findings that IL‐36 cytokines potentiate the production of Th17 cytokines contributing to the cytokine network in psoriasis .…”
Section: Discussionsupporting
confidence: 84%
“…Recently, it was reported that direct intradermal injection of IL‐36 cytokines (combination of α, β and γ) into mouse ear skin produced ear swelling as observed in the current study. The major component of inflammatory infiltration from our observations was also myeloid cells, specifically macrophages, which is similar to that in the IL‐23 model . Overall, the inflammatory phenotype of the IL‐36α ear injection model recapitulated key features of psoriatic skin lesions .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…As expected, prophylactic dosing (starting at day 0, prior to the injection of the MC and onset of disease) of the anti‐IL‐23p40 completely prevented MC‐induced increases in ear thickness, dermal and epidermal area, and gene expression. Interestingly, these data differ from the same anti‐IL‐23p40 antibody tested by our group prophylactically in the IL‐23 ear injection model, in which the same dose only achieved approximately 50% inhibition of several endpoints . As noted in this paper, the decreased efficacy in the ear injection model may be driven by an IL‐23‐independent component (e.g.…”
Section: Discussioncontrasting
confidence: 71%
“…Repeated intradermal injection of IL‐23 to mice has been used as a mechanistic model that recapitulates many key features of psoriasis . These models have been useful in understanding skin inflammation associated with activation of this pathway and evaluating novel therapeutics.…”
Section: Introductionmentioning
confidence: 99%